Genological stratification of diplomatic discourse on Twitter : Based on the material of the countries of the Romance and Germanic language areas - Ponomarenko, Olga; Smushchynska, Iryna; Popivniak, Olena; Tyshchenko, Olena; Kovalchuk, Valentyna (Linguistics and Culture Review, 2021)
Scientific and technological progress with all its achievements has affected various spheres of human life. Philological disciplines, including communicative linguistics, are no exception. The means of communication have changed significantly in recent decades. No one is surprised by computer-mediated interactions, the internet has become available, and it is not difficult for many people to use personal electronic gadgets. These new developments have affected both the sphere of personal communication, including business, work, and professional relationships. All this is also relevant for diplomatic discourse, the evolutionary leap of which has taken place literally in half a century: from isolation and going beyond political discourse to the level of independent development to its current functioning with the active use of the entire palette of communication tools, methods, and techniques, including Internet resources, in particular, microblogs. The purpose of this article is to determine, describe and make an attempt to predict the levels and structure of genres of diplomatic discourse in the coming decades using examples of its manifestations on Twitter in the best traditions of classical linguistics schools and considering the achievements of new research areas in linguistics.